ActiveStorage: A Storage Server with Mobile Code Engine - Golm, Michael; Wawersich, Christian; Felser, Meik; Kleinöder, Jürgen (2001)
UnivIS-Import:2016-06-30:Pub.2001.tech.IMMD.IMMD4.active
Keywords: active storage; mobile code; JX; operating system; components

A Java Operating System as the Foundation of a Secure Network Operating System - Golm, Michael; Felser, Meik; Wawersich, Christian; Kleinöder, Jürgen (2002)
UnivIS-Import:2016-06-30:Pub.2002.tech.IMMD.IMMD4.ajavao
Keywords: JX; Sicherheit; security

A Retargetable JIT Compiler for Java - Golm, Michael; Kleinöder, Jürgen; et al. (1999)
UnivIS-Import:2016-06-27:Pub.1999.tech.IMMD.IMMD4.aretar

Beyond Address Spaces - Flexibility, Performance, Protection, and Resource Management in the Type-Safe JX Operating System - Golm, Michael; Bellosa, Frank; Kleinöder, Jürgen (HotOS 2001, 2001)
Early type-safe operating systems were hampered by poor performance. Contrary to these experiences we show that an operating system that is founded on an object-oriented, type-safe intermediate code can compete with MMU-based microkernels concerning performance while widening the realm of possibilities. Moving from hardware-based protection to software-based protection offers new options for operating system quality, flexibility, and versatility that are superior to traditional process models based on MMU protection. However, using a type-safe language-such as Java-alone, is not sufficient to achieve an improvement. While other Java operating systems adopted a traditional process concept, JX implements fine-grained protection boundaries. The JX System architecture consists of a set of Java components executing on the JX core that is responsible for system initialization, CPU context switching and low-level domain management. The Java code is organized in components which are loaded into domains, verified, and translated to native code. JX runs on commodity PC hardware, supports network communication, a frame grabber device, and contains an Ext2-compatible file system. Without extensive optimization this file system already reaches a throughput of 50% of Linux.
UnivIS-Import:2015-04-16:Pub.2001.tech.IMMD.IMMD4.beyond
Keywords: protection; performance; java; jx; resource management; type-safe; Betriebssystem

Dynamic Software Update of Resource-Constrained Distributed Embedded Systems - Felser, Meik; Kapitza, Rüdiger; Kleinöder, Jürgen; Schröder-Preikschat, Wolfgang (Embedded System Design: Topics, Techniques and Trends, 2007)
Changing demands, software evolution, and bug fixes require the possibility to update applications as well as system software of embedded devices. Systems that perform updates of resource-constrained nodes are available, but most approaches require a complete restart of the node after installing or updating software. Restarting the node results in the loss of important system state, such as routing information or sensor calibration values. Rebuilding this information requires time and energy. In this paper we present an online state-preserving update system for sourceconstrained nodes. A remote incremental linking approach is used to generate node-specific and execution-state dependent code. Compiler-generated symbol, relocation, and debugging information is used to determine whether a dynamic update of the running system is possible and how it can be achieved. © International Federation for Information Processing 2007.
UnivIS-Import:2015-04-16:Pub.2007.tech.IMMD.IMMD4.dynami
Keywords: Dynamic update; ELF; Managed nodes; Relocations

Execution Time Limitation of Interrupt Handlers in a Java Operating System - Felser, Meik; Golm, Michael; Wawersich, Christian; Kleinöder, Jürgen (Tenth ACM SIGOPS European Workshop, 2002)
Device drivers are a very critical part of every operating system. They often contain code that is executed in interrupt handlers. During the execution of interrupt handlers, the processing of some other interrupts is usually disabled. Thus errors in that code can compromise the whole system.This paper describes an approach to ensure that an interrupt handler is not allowed to use more than a specified amount of time. Our approach is based on a Java operating system and consists of a combination of verification at compilation time and run-time checks.
UnivIS-Import:2015-04-16:Pub.2002.tech.IMMD.IMMD4.execut
Keywords: JX; verifier; driver

Fine-grained parallel computation in the PM/OM object model - Kleinöder, Jürgen; et al. (1994)
UnivIS-Import:2016-06-23:Pub.1994.tech.IMMD.IMMD4.finegr

GI/ITG KuVS Fachgespräche Energiebewusste Systeme und Methoden und Systemsoftware für Pervasive Computing - Kleinöder, Jürgen; et al. (Universität Erlangen-Nürnberg, 2005)
UnivIS-Import:2015-05-08:Pub.2005.tech.IMMD.IMMD4.quanti

Hierarchical schedulers in the PM System-Architecture - Kleinöder, Jürgen; et al. (1994)
UnivIS-Import:2016-06-23:Pub.1994.tech.IMMD.IMMD4.hierar

Implementing Real-Time Actors with MetaJava - Golm, Michael; Kleinöder, Jürgen (Object-Oriented Technology - ECOOP'97 Workshop Reader, 1997)
UnivIS-Import:2015-04-16:Pub.1997.tech.IMMD.IMMD4.implem

Java - die Embedded-Sprache von morgen? - Kleinöder, Jürgen (Design & Elektronik, 1997)
UnivIS-Import:2015-03-05:Pub.1997.tech.IMMD.IMMD4.javadi

Jumping to the Meta Level: Behavioural Reflection can be fast and flexible - Golm, Michael; Kleinöder, Jürgen (Meta-Level Architectures and Reflection, 1999)
Fully reflective systems have the notion of a control transfer from base-level code to meta-level code in order to change the behavior of the base-level sytem. There exist various opinions on how the programming model of a meta architecture has to look like. A common necessity of all models and sytems is the need to intercept messages and operations, such as the creation of objects. We analyze the trade-offs of various message interception mechanism for Java. We show their impact on the meta-level programming model and performance. We demonstrate that it is beneficial to integrate the interception mechanism with the virtual machine and the just-in-time compiler.
Keywords: Meta objects; Reflexion; Java

JX: Eine adaptierbare Java-Betriebssystemarchitektur - Golm, Michael; Kleinöder, Jürgen (2000)
UnivIS-Import:2016-06-30:Pub.2000.tech.IMMD.IMMD4.jxeine
Keywords: JX; Systemarchitektur; Komponenten; metaXa

MetaJava: An Efficient Run-Time Meta Architecture for Java - Kleinöder, Jürgen; Golm, Michael (Proceedings Fifth International Workshop on Object Orientation in Operating Systems, 1996)
UnivIS-Import:2015-04-16:Pub.1996.tech.IMMD.IMMD4.metaja

MetaJava - A Platform for Adaptable Operating-System Mechanisms - Kleinöder, Jürgen; Golm, Michael (Object-Oriented Technology - ECOOP'97 Workshop Reader, 1997)
UnivIS-Import:2015-04-16:Pub.1997.tech.IMMD.IMMD4.metaja

MetaJava - Golm, Michael; Kleinöder, Jürgen (STJA '97, 1997)
UnivIS-Import:2015-04-16:Pub.1997.tech.IMMD.IMMD4.metaja_1

Meta Objects for Access Control: Role-Based Principles - Kleinöder, Jürgen; et al. (Information Security and Privacy, 1998)
UnivIS-Import:2015-04-16:Pub.1998.tech.IMMD.IMMD4.metaob

metaXa and the Future of Reflection - Golm, Michael; Kleinöder, Jürgen (Proc. of the OOPSLA '98-Workshop on Reflective Programming in C++ and Java, 1998)
UnivIS-Import:2015-04-16:Pub.1998.tech.IMMD.IMMD4.metaxa

Object- and memory management architecture - Kleinöder, Jürgen (1992)
UnivIS-Import:2016-06-23:Pub.1992.tech.IMMD.IMMD4.object

Objekt- und Speicherverwaltungs-Architektur - Kleinöder, Jürgen (1992)
UnivIS-Import:2016-06-23:Pub.1992.tech.IMMD.IMMD4.objekt

OctoPOS: A Parallel Operating System for Invasive Computing - Oechslein, Benjamin; Schedel, Jens; Kleinöder, Jürgen; Bauer, Lars; Henkel, Jörg; Lohmann, Daniel; Schröder-Preikschat, Wolfgang (Proceedings of the International Workshop on Systems for Future Multi-Core Architectures (SFMA'11), 2011)
UnivIS-Import:2015-04-16:Pub.2011.tech.IMMD.IMMD4.octopo
Keywords: invasive computing; operating system; multi core; many core

PM Systemarchitektur - Kleinöder, Jürgen (Verteilte Systeme - Grundlagen und zukünftige Entwicklung aus der Sicht des SFB 182 "Multiprozessor- und Netzwerkkonfigurationen", 1994)
UnivIS-Import:2015-04-20:Pub.1994.tech.IMMD.IMMD4.pmsyst

PM Systemarchitektur - Kleinöder, Jürgen (1992)
UnivIS-Import:2016-06-23:Pub.1992.tech.IMMD.IMMD4.pmsyst

RepliXa - Ein Framework zur transparenten und anpassbaren Objektreplikation - Golm, Michael; Kleinöder, Jürgen; et al. (1999)
UnivIS-Import:2016-06-27:Pub.1999.tech.IMMD.IMMD4.replix

Robust and Efficient Software Management in Sensor Networks - Schröder-Preikschat, Wolfgang; Kapitza, Rüdiger; Kleinöder, Jürgen; Felser, Meik; Karmeier, Katja; et al. (2nd IEEE/ACM International Conference on Communication System Software and Middleware (COMSWARE 2007), 2007)
Software deployment and updating of deployed code is a critical topic in the area of wireless sensor networks (WSN). Reasons are unreliable network connectivity, resource limitations of devices, and energy restrictions in general. Consequently, software deployment has to be performed with great care otherwise resources might be wasted or nodes become unavailable due to failed updates. The overall objective for software management in sensor networks is to enable a robust and efficient way to build deployable software images that take into account all the needs from application requirements to node-specific resource restrictions. In this article, we outline the current state-of-theart for software management in WSN and (network-based) sensor network (re-)programming. We provide insights into three different approaches enabling a more comprehensive management of WSN while challenging the robustness and efficiency of software configurations and reprogramming. Additionally, we outline research challenges in the area of software management and sensor network operation. © 2007 IEEE.
UnivIS-Import:2015-04-16:Pub.2007.tech.IMMD.IMMD4.robust
Keywords: RDSP

The JX Operating System - Golm, Michael; Felser, Meik; Wawersich, Christian; Kleinöder, Jürgen (General Track 2002 USENIX Annual Technical Conference, 2002)
UnivIS-Import:2015-04-16:Pub.2002.tech.IMMD.IMMD4.thejxo
Keywords: JX; operating system

The Role of IPC in the Component-Based Operating System JX - Wawersich, Christian; Felser, Meik; Golm, Michael; Kleinöder, Jürgen (Proceedings of the 5th ECOOP Workshop on Object-Orientation and Operating Systems, 2002)
UnivIS-Import:2015-04-16:Pub.2002.tech.IMMD.IMMD4.therol
Keywords: JX

Transparent and Adaptable Object Replication Using a Reflective Java - Kleinöder, Jürgen; Golm, Michael (1996)
UnivIS-Import:2016-06-27:Pub.1996.tech.IMMD.IMMD4.transp

Ubiquitous Computing and the Need for a New Operating System Architecture - Golm, Michael; Kleinöder, Jürgen (2001)
UnivIS-Import:2016-06-30:Pub.2001.tech.IMMD.IMMD4.ubiqui
Keywords: JX

Understanding the Performance of the Java Operating System JX using Visualization Techniques - Golm, Michael; Wawersich, Christian; Felser, Meik; Kleinöder, Jürgen (Proceedings of the Joint ACM Java Grande - ISCOPE 2002 Conference, 2002)
In the JX project, a complete operating system using the type-safe, object-oriented language Java is built. One of the major challenges is achieving a performance that is competitive to mainstream operating systems, such as Linux or Solaris. This paper concentrates on optimizing byte-code-to-nativecode translator and instrumentation/visualization tools to locate performance problems to achieve good performance.
UnivIS-Import:2015-04-16:Pub.2002.tech.IMMD.IMMD4.unders_21
Keywords: JX; Performance; GC; Garbage collection; visualization

Understanding the Performance of the Java Operating System JX using Visualization Techniques - Golm, Michael; Wawersich, Christian; Felser, Meik; Kleinöder, Jürgen; et al. (2001)
UnivIS-Import:2016-06-30:Pub.2001.tech.IMMD.IMMD4.unders
Keywords: Performance; JX; Visualization; Sampling; Tracing